2012
DOI: 10.1186/1744-8069-8-34
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen Activated Protein Kinase Phosphatase-1 Prevents the Development of Tactile Sensitivity in a Rodent Model of Neuropathic Pain

Abstract: BackgroundNeuropathic pain due to nerve injury is one of the most difficult types of pain to treat. Following peripheral nerve injury, neuronal and glial plastic changes contribute to central sensitization and perpetuation of mechanical hypersensitivity in rodents. The mitogen activated protein kinase (MAPK) family is pivotal in this spinal cord plasticity. MAPK phosphatases (MKPs) limit inflammatory processes by dephosphorylating MAPKs. For example, MKP-1 preferentially dephosphorylates p-p38. Since spinal p-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 44 publications
2
25
1
Order By: Relevance
“…Moreover, they demonstrated that luciferase expression using in vivo PEI transfection in chicken embryonic neurons was similar to that obtained in primary brain cells in vitro at the optimal N/P ratio of 9. These data are also in accordance with previous data from our laboratory in which in vivo gene induction using PEI was demonstrated in rat spinal cord in a model of neuropathic pain (Ndong et al, 2012).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, they demonstrated that luciferase expression using in vivo PEI transfection in chicken embryonic neurons was similar to that obtained in primary brain cells in vitro at the optimal N/P ratio of 9. These data are also in accordance with previous data from our laboratory in which in vivo gene induction using PEI was demonstrated in rat spinal cord in a model of neuropathic pain (Ndong et al, 2012).…”
Section: Discussionsupporting
confidence: 94%
“…Levels of mRNA were determined as described previously (Ndong et al, 2012). Briefly, 1 g of total RNA from each sample was reverse transcribed into cDNA using the ScriptTM Reverse Transcription Supermix (BioRad, Hercules, CA) in the following conditions: 5 min at 25 • C, 30 min at 42 • C and 5 min at 85 • C. We quantified the expression of TNF-␣ (59 • C), IL-6 (60 • C), IL-10 (59 • C), CD14 (57 • C), CD68 (58 • C), GFP (60 • C) and ␤-actin (57 • C) using the SsoAdvancedTM Universal SYBR Green Supermix (BioRad, Hercules, CA) in the following conditions: 1 cycle of 98 • C for 30 s, 45 cycles of 98 • C for 15 s followed by 30 s of the primerspecific annealing temperature.…”
Section: Rna Isolation and Quantitative Real Time (Rt)-pcrmentioning
confidence: 99%
“…The RNA was isolated from THP-1 macrophages and primary macrophages using ReliaprepTM RNA Cell Miniprep System (Promega, Madison, WI), according to the manufacturer’s protocols. Levels of mRNA were determined as described previously (Ndong, et al, 2012). Complementary DNA (cDNA) was synthesized from 1 μg of total RNA from each sample using Script Reverse Transcription Supermix (BioRad, Hercules, CA) under the following conditions: 5 min at 25°C, 30 min at 42°C, and 5 min at 85°C.…”
Section: Methodsmentioning
confidence: 99%
“…Possible reasons for resistance to the development of chronic pain in genetically similar animals (9294) are currently being explored. Combined with strategies aimed at understanding endogenous factors (95, 96) associated with the natural resolution of pain, as observed in many chronic neuropathic pain patients over time (97), such studies could point to genetic and epigenetic clues to identify those patients who are most at risk to develop (98) or limit chronic pain, thereby linking the laboratory to the reality of the clinical world. Indeed, resolution from injury may be an active process that engages signaling molecules such as the resolvins and the protectins (95, 99).…”
Section: Preclinical Challenges In Identification Of Pain Targetsmentioning
confidence: 99%